THE ROLE OF VILLAGE-OWNED ENTERPRISES (BUMDES) IN THE DEVELOPMENT OF INTEGRATED WASTE MANAGEMENT SITES (TPST) IN KEDUNGTURI VILLAGE, TAMAN, SIDOARJO - Hanim, Masfufah; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to describe and analyze the role of Village-Owned Enterprises (BUMDes) in the development of Integrated Waste Management Sites (TPST) in Kedungturi Village, Taman District, Sidoarjo Regency. Method: The use is qualitative descriptive research, with data collection through interviews, observations, and documentation, as well as data analysis using the Miles and Huberman model. Results: show that BUMDes have successfully carried out their role in waste management through four indicators from the role theory of Biddle & Thomas in Sarwono: First, the role of Hope, which reflects the expectations of the community. Second, the role of norms, which shape managers' behavior. Third, the form of behavior seen in real actions in management. And finally, Evaluation & Sanctions, which strengthens management accountability. Novelty: this research lies in the application of role theory in the context of environmental management at the village level, as well as providing insight into how BUMDes can function as agents of change in effective and efficient waste management.